Unique Cellulase Enzyme of Bacillus firmus From Organic Waste - ., Purkan; ., Sumarsih; A, Rachmadani D (UNEJ e-Proceeding, 2014)
The objectives of this research are to isolate cellulolytic bacteria from liquid fermentation of organic waste, to determine the optimum conditions of cellulose enzyme production and characterize of crude extract cellulase enzyme activity, including pH and optimum temperature. Cellulolytic bacteria was isolated with pour plate method using specific media CMC (Carboxymethyl Celullose) and incubated at  the temperature of 370C for 24 hours. The activity of cellulolytic bacteria can be seen by the presence of transparent zone around the place where colony grows. The identification of isolates was done macroscopically, microscopically and biochemistry. Cellulolytic enzyme activity was determined with Miller method to CMC substrate. In this research, 2 isolates of cellulose producer bacteria with the biggest cellulolytic index of 1,903 (DA1) was obtained. Optimum condition of cellulose enzyme production by the bacteria was at hour-24 with the optimum molasses concentration of 0,4% and producing enzyme activity which is 0,04802 U/mL. The cellulose enzyme activity which was produced by Bacillus firmus isolate showed that the crude enzyme has  optimum activity at  pH 5 and temperature of 500C. Keywords: organic waste, Bacillus firmus,  cellulolytic bacteria, cellulose